Hygric and thermal properties of hemp-lime plasters. (1st February 2016) - Mazhoud, Brahim; Collet, Florence; Pretot, Sylvie; Chamoin, Julien
Abstract: Hemp-lime mortars are generally used as indoor insulating plasters of building envelopes. They can be applied in thick coat to allow high enough hygrothermal performances to be reached in retrofit case. This study investigates hygric and thermal properties of two hemp-lime plasters. These plasters are made with the same lime-based binder and differ from their kind of hemp shiv. The two kinds of hemp shiv are defibered but one is smaller than the other. This experimental study is based on the measurement of sorption isotherm, water vapour permeability, moisture buffer value and thermal properties (conductivity and diffusivity). The effect of temperature on moisture buffer value and on thermal properties is also investigated. It is shown that hemp-lime plasters are hygroscopic and breathable materials. They are good hygric regulators according to the Nordtest classification and their moisture buffering ability is slightly impacted by temperature in the range from 11° to 23 °C. The hemp-lime plaster with the smallest hemp shiv is a better hygric regulator than the one with the biggest hemp shiv. Hemp-lime plasters show a quite low thermal conductivity, around 0.2 W/(m.K). The hemp-lime plaster with the smallest hemp shiv is slightly more conductive than the one with the biggest hemp shiv. The temperature does not impact thermal conductivity at dry state. At wet state, for a given relative humidity, when the temperature increases the thermal conductivity decreases simultaneously with water content. This study underlines that hemp-lime plasters show high hygrothermal qualities. Highlights: Hygric and thermal properties of Hemp-lime plasters are investigated. Hemp-lime plasters are good hygric regulators. The moisture penetration depth is estimated. Hemp-lime plasters are pertinent solution for thermal retrofit. Effect of temperature on hygric and thermal properties is investigated.